INSTITUTIONAL OWNERSHIP, AUDIT QUALITY, ESG, AND TAX AVOIDANCE: Evidence from Energy Sector Mining Firms - Rahayu Setianingrum; Yenny Dwi Handayani (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This research examines whether institutional ownership, audit quality, and Environmental, Social, and Governance (ESG) influence corporate tax avoidance. The study focuses on mining companies in the energy sector that were publicly traded on the Indonesia Stock Exchange between 2020-2023. The research sample was selected through purposive sampling based on several predetermined criteria aligned with the study objectives. The analysis relies on secondary data obtained from corporate financial reports. To test the proposed relationship, that data were analysed using multiple linier regression with support of SPSS version 25. The empirical findings show that institutional ownership does not have a significantly effect on tax avoidance. In contrast, audit quality and ESG practices significantly influence tax avoidance. These results indicate that external monitoring through high-quality audits and the implementation of ESG principles may affect corporate decisions related to tax avoidance behaviour.